PERAN TAMPILAN PRODUK, KEAMANAN DAN KEMUDAHAN PADA KEPUTUSAN BERTRANSAKSI MENGGUNAKAN JASA PENGIRIMAN SHOPEE - Aris Tri Haryanto; Septiana Novita Dewi (Jurnal Bisnis Terapan, 2021)
Abstract This research aimed to test and analyze the role of product display, security and ease of transaction decisions using Shopee's shipping services. This research was conducted in the Surakarta area. The object of this research is consumers who have transacted using the Shopee application. The population in this study were consumers who had shopped using the Shopee application who had made transactions at the end of 2019. The sample determination process was carried out based on consumer experience in using the Shopee application. Furthermore, it was ensured that the consumers who were the samples of this study met the specified criteria and were willing to fill out the questionnaire. If they were not willing and do not meet the criteria, then the consumer was skipped and then researcher looked for other consumers who met the sample criteria. By using this technique, not all populations in this study had the same opportunities as research samples. In this study the sample was 56 respondents. This study resulted in a regression equation, it can be seen that product appearance, security and convenience have a positive effect on the decision to transact using Shopee's shipping services. The results of the t-statistical test show that product appearance, security and convenience partially have a significant effect on the decision to transact using Shopee's delivery service Keywords: Product Display, Security and Ease, Transaction Decision.